Replacement Core Switch, Distribution Switch, dan Access Switch pada Perusahaan Manufaktur Makanan dan Minuman - Mardhatillah, Andi Amaliah; Anwar, Radial (eProceedings of Applied Science, 2024)
The rapid development of technology is forcing companies to continue to innovate, including in computer network device updates to support increasingly complex business needs. this report aims to comprehensively explain the process replacement of Core Switches, Distribution Switches, and Access Switches at a food and beverage manufacturing company. This process includes preparatory stages, initial configuration devices, pre-migration documentation, migration execution, post-migration monitoring, error handling, and preparation of User Acceptance Testing (UAT) documents. Method used in this report is the waterfall method consists of analysis, design, implementation, testing, and stages maintenance. The result of replacing a network device shows significant performance improvements, making network is faster and more efficient and reduces risk operational disruption. The main conclusions of this report is the importance of careful planning and careful execution in maintaining the stability and reliability of the company network, as well as the successful process of replacing key network devices in a food and beverage manufacturing company environment. Keywords— Replacement switch, Food Company and Drinks, Waterfall Method